Mikołaj Rej a „sprawa litewska” – uwagi Pana z Nagłowic o unii (lubelskiej) i Litwinach - Dybek, Dariusz (Tematy i Konteksty, 2019)
Mikolaj Rej was not only one of the most notable 16th century Polish writers, but also an active member of the parliament. Among others, he worked on the Polish-Lithuanian issues. Based on the governmental documentation, Rej was engaged in these issues from 1542 onwards. He also dedicated a few pieces of writing to the matter, the most important of which is a poem written around 1567 entitled ‘Union with Lithuania’. In the poem he condemned the sluggishness in debating the unification of the two countries, but emphasized that the Lithuanians should have taken a greater interest in the matter, since Poland could have helped their fights with the Eastern neighbours. As he did during the parliamentary sessions, the author also stressed the need for electing a common king. Despite hoping for a quick resolution and unification, Rej did not regard Lithuania as an equal parter for Poland. Based on a few poets, the author seems to think of the Lithuanians as of a backward nation (e.g. their table manners during the feasts and the use of primitive language). It is worth noting that Rej treated the Lithuanian aristocracy differently. While describing the clans and noble families (e.g. the Radziwiłł family or the Chodkiewicz family), he emphasised their patriotism and bravery. Rej’s remarks on the Lithuanians and the union did not stand out from the common opinion at the time. They could represent the feelings of a typical member of the Polish gentry.